Significance of tempering methods on sorghum kernel, flour, and baking properties - Yoganandan, Mohana (Kansas State University, 2020)
The sorghum milling industry is not completely established unlike the corn and wheat milling industries. Current sorghum milling methods may result in lower flour yield, high milling losses, flour contamination, inconsistent flour quality, and greater damaged starch content. Appropriate tempering processes could improve the sorghum milling and bread making properties. Direct and indirect methods were applied to investigate the effects of cold water, hot water, and steam tempering methods on the sorghum kernel, flour and bread making properties. In this study, three sets of tempering methods were carried out: (i) cold (16 and 18% m.c at 24°C for 24 h); (ii) hot (16 and 18% m.c at 60°C for 12, 18, and 24 h); and (iii) steam (at 20 psi for 5, 10, and 15 sec). Single kernel characteristics (SKCS), abrasive hardness index (AHI), bulk, true, and tapped density, coefficient of static and rolling friction were measured for white and waxy white sorghum kernels. The cold water tempered sorghum kernels had both lower SKCS hardness and AHI than kernels treated with other tempering methods. Overall tempering condition and tempering moisture content was found to have significant effect on the physical properties i.e. bulk, tapped, and true density, and angle of repose than material properties i.e. coefficient of static and rolling friction. The effects of tempering methods on the roller milling performance and flour quality were also evaluated. The developed laboratory-scale roller milling flowsheet consists of four break rolls and eight reduction rolls. Hot water tempering method (16% m.c at 60°C for 18 h) led to better separation of bran and endosperm, due to toughening of the bran, which allowed gradual scraping of the endosperm from the bran without negatively impacting flour quality characteristics i.e. particle size distribution, flour yield, protein content, ash, damaged starch content, and moisture content of the white and waxy white sorghum flours. The effects of tempering methods on the bread making characteristics were also evaluated. Bread produced from the flour obtained from milling sorghum kernels tempered with cold water (18% m.c for 24 h) and hot water (16% m.c at 60°C for 18 h) displayed better bread making properties i.e. low firmness, high resilience, greater volume index, higher number of cells, and thin cell walls when compared to other tempering conditions. Hot water tempering treatment (16% m.c at 60°C for 18 h) could be a better pretreatment process for milling white and waxy white sorghum kernels without negatively impacting the flour and bread making quality characteristics.
Keywords: Sorghum; Tempering; Roller milling; Kernel properties; Flour properties; Baking properties